Novel Cucumis enzymes associated with host-specific disease resistance to Phytophthora melonis Katsura. Issue 1 (1st January 2020) - Nasr-Esfahani, Mehdi; Hashemi, Lida; Nasehi, Abbas; Nasr-Esfahani, Ava; Nasr-Esfahani, Arman
Abstract: The hemibiotrophic oomycetes are significant threats to a wide range of Cucurbitaceae species, causing substantial losses of plant productions. Particularly, Phytophthora melonis Katsura evokes severe symptoms, thus dramatically limiting the yield in cucumber. However, the information about cucumber– P. melonis interaction is still limited. This study explored the changes in the activities of phenylalanine ammonia-lyase (PAL), peroxidase (POX), catalase (CAT), superoxide dismutase (SOD) and polyphenol oxidase (PPO) in cucumber roots of two resistant genotypes (Soheil and Ramezz), one moderately resistant genotype (Baby) and three highly susceptible genotypes (Extrem, Mini 6–23 and Yalda), over the time courses of 7, 14 and 21 days after inoculation (DAI). The results indicated that the activities of defense-related enzymes differed between the resistant and highly susceptible genotypes. Although the defense-related enzymatic activities were elevated sharply in the resistant and moderately resistant genotypes after inoculation, no significant correlations were present between the activity trends of PPO, SOD and CAT and resistance characteristics. Moreover, no significant changes in enzyme activities were found in the control plants, non-inoculated plants of the six genotypes during the testing period. Altogether, the resistance of cucumber to P. melonis is related to POX and PAL activities, but does not show relationship with PPO, SOD and CAT activities. Studying the physiological metabolic pathways of POX and PAL appears to be an important direction in research to elucidate the resistance to P. melonis in cucumber genotypes.